2015
DOI: 10.1038/srep14124
|View full text |Cite
|
Sign up to set email alerts
|

CD8+NKT-like cells regulate the immune response by killing antigen-bearing DCs

Abstract: CD1d-dependent NKT cells have been extensively studied; however, the function of CD8+NKT-like cells, which are CD1d-independent T cells with NK markers, remains unknown. Here, we report that CD1d-independent CD8+NKT-like cells, which express both T cell markers (TCRβ and CD3) and NK cell receptors (NK1.1, CD49b and NKG2D), are activated and significantly expanded in mice immunized with GFP-expressing dendritic cells. Distinct from CD1d-dependent NKT cells, CD8+NKT-like cells possess a diverse repertoire of TCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…Reduced pretransplant serum levels of IL-12, a major driver for NK cell activation (29), may account for the lower numbers of circulating NK cells in high-risk patients, supporting previous observations that, in contrast with its proinflammatory effects, IL-12 is associated with prolonged graft survival (30). CD8 + NK T cells with regulatory properties have also been described (31), and their reduced number may expose patients to higher risk of rejection and a subsequent graft failure. Finally, we found that patients with high gene risk score had a significant reduction in the expression of programmed cell death 1 gene (not shown), a major regulator of T cell exhaustion (32) and of regulatory function (33), both important functions in preventing AR.…”
Section: Discussionsupporting
confidence: 76%
“…Reduced pretransplant serum levels of IL-12, a major driver for NK cell activation (29), may account for the lower numbers of circulating NK cells in high-risk patients, supporting previous observations that, in contrast with its proinflammatory effects, IL-12 is associated with prolonged graft survival (30). CD8 + NK T cells with regulatory properties have also been described (31), and their reduced number may expose patients to higher risk of rejection and a subsequent graft failure. Finally, we found that patients with high gene risk score had a significant reduction in the expression of programmed cell death 1 gene (not shown), a major regulator of T cell exhaustion (32) and of regulatory function (33), both important functions in preventing AR.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, in women with human papillomavirus (HPV)-associated cervical neoplasia, there are increased levels of CD28 − , T EM , and CD16 + CD56 + CD8 + T-cells in peripheral blood, probably associated with the chronic infection with HPV (44). As we mentioned above, NK-like CD8 + T-cells possess a diverse TcR repertoire and there is evidence that these cells can function as antigen-specific suppressive cells that regulate the immune response through killing antigen-bearing dendritic cells (13). The class-I MHC-restricted T-cell-associated molecule (CRTAM) has been shown to be expressed only on activated class-I MHC-restricted T-cells, including NK-like CD8 + and conventional CD8 + T-cells.…”
Section: Nk-like Cd8+ T-cells In Virus Infection and Immunosenescencementioning
confidence: 99%
“…These lymphocytes change the spectrum of their target‐cell specificity and the mechanism of cell death induction, and their interaction with target cells is not species‐specific. It is probable that these are NKT lymphocytes, which have been shown to be capable of killing target cells with “alien” MHC components by perforin/granzyme‐dependent cytolysis .…”
Section: Resultsmentioning
confidence: 99%